2022
DOI: 10.1186/s12883-022-02907-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk and severity of SARS-CoV-2 reinfection among patients with multiple sclerosis vs. the general population: a population-based study

Abstract: Background We conducted this study to compare the risk of reinfection between multiple sclerosis (MS) patients and a control group without MS. Method In this retrospective study, data of all SARS-CoV-2 tests (n = 793,301) and almost all MS patients (n = 10,639) in Isfahan province were collected from January 01, 2020 to August 22, 2021. Of the 2196 MS patients and 793,301 persons from the general population who had been tested at least once, 3 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…All of the 23 included studies were case–control studies, and the quality of all of the literature was identified as high according to the NOS ( Table 2 ). These studies were conducted in the the United States (USA), 17 18 19 20 the Netherlands, 21 Austria, 15 Spain, 22 Sweden, 23 24 25 Iran, 26 27 28 Chile, 29 Italy, 9 30 31 France, 30 Australia, 6 Poland, 32 Canada, 33 and Singapore. 34 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All of the 23 included studies were case–control studies, and the quality of all of the literature was identified as high according to the NOS ( Table 2 ). These studies were conducted in the the United States (USA), 17 18 19 20 the Netherlands, 21 Austria, 15 Spain, 22 Sweden, 23 24 25 Iran, 26 27 28 Chile, 29 Italy, 9 30 31 France, 30 Australia, 6 Poland, 32 Canada, 33 and Singapore. 34 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the level of protection conferred by vaccination in PLWMS with insufficient humoral immunity, particularly those on anti-CD20 agents is unknown. Concerns exist regarding the effectiveness of SARS-CoV-2 vaccines in PLWMS in light of these findings and a slightly decreased protection against SARS-CoV-2 reinfection in this population ( Barzegar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%